Roman funerary rituals in Mutina (Modena, Italy) - Riso, Federica Maria (Archaeopress Roman archaeology, 2023)
This study presents the results of a research project undertaken in collaboration with the University of Huddersfield. The project sought to identify and reconstruct the funerary space and rituals of the necropolis in Mutina (now Modena) in the period between the first century BC and second century AD.